Slip band-grain boundary interactions in commercial-purity titanium - Guo, Y; Britton, T; Wilkinson, A (Elsevier, 2014)
The interaction between slip bands and grain boundaries in commercial-purity titanium was examined using cross-correlation-based electron backscatter diffraction. At a low strain level, three types of interactions were observed: blocked slip band with stress concentration; slip transfer; and blocked slip band with no stress concentration. The stress concentration induced by the blocked slip band was fitted with Eshelby's theoretical model, from which a Hall-Petch coefficient was deduced. It was found that the Hall-Petch coefficient varies with the individual grain boundary. We investigated the geometric alignment between the slip band and various slip systems to the neighbouring grain. Stress concentration can be induced by the blocked slip band if the slip system is poorly aligned with prismatic, pyramidal or basal slip systems in the neighbouring grain. Transfer of slip across the boundary occurs when there is good alignment on prismatic or pyramidal slip systems. Other stress-relieving mechanisms are possible when the best alignment is not with the slip system that has the lower critical resolved shear stress. ©2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.